2021
DOI: 10.1182/blood-2021-149880
|View full text |Cite
|
Sign up to set email alerts
|

Novel Salvage Regimens Lead to Better Response and Survival in Relapsed Refractory Classic Hodgkin Lymphoma after Autologous Stem Cell Transplant

Abstract: Introduction: Clinical trials of novel salvage therapies (ST) have encouraging outcomes for relapsed/refractory classic Hodgkin lymphoma (R/R cHL) after autologous stem cell transplant (ASCT); yet studies comparing novel ST with conventional salvage chemotherapy are lacking. In a single center cohort, we demonstrated that bendamustine/brentuximab (BBV) had higher overall response rates (ORR) and complete response (CR) rates in ASCT-eligible R/R cHL (Desai et al JCO, 2021). Herein we report comparative outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Spinner et al [16] also reported an enhanced outcome for the cohort of patients receiving pre-ASCT immunotherapy relative to those receiving platinum-based chemotherapy: 4-year PFS was 91% vs. 66%. This observation is similar to that reported by a multicenter study comprising 854 patients with R/R undergoing HDT/ASCT across the United States [35]. In this report, Desai et al found that patients receiving the combination of BV/nivolumab had higher CR rates and PFS relative to those receiving conventional chemotherapy, while those receiving only BV had lower CR rates.…”
Section: Discussionsupporting
confidence: 90%
“…Spinner et al [16] also reported an enhanced outcome for the cohort of patients receiving pre-ASCT immunotherapy relative to those receiving platinum-based chemotherapy: 4-year PFS was 91% vs. 66%. This observation is similar to that reported by a multicenter study comprising 854 patients with R/R undergoing HDT/ASCT across the United States [35]. In this report, Desai et al found that patients receiving the combination of BV/nivolumab had higher CR rates and PFS relative to those receiving conventional chemotherapy, while those receiving only BV had lower CR rates.…”
Section: Discussionsupporting
confidence: 90%
“…In a preliminary retrospective multicenter study, we observed that CPI-based salvage regimens resulted in significantly higher PFS compared to platinumbased chemotherapy. 20 Herein, we report the final results of our multicenter retrospective cohort study of 14 participating institutions, evaluating novel salvage regimens comparative to conventional chemotherapy in R/R cHL who underwent ASCT.…”
Section: Introductionmentioning
confidence: 99%
“…A large multi-institution retrospective study compared response rates and outcomes among various salvage regimens for R/R cHL patients who underwent ASCT. This data was presented at the American Society of Hematology (ASH) Annual Meeting in 2021 [ 94 ]. The combination of BV-bendamustine had a higher ORR (92% vs. 79%, p < 0.001) and CR rates (80% vs. 49%, p < 0.001) compared with platinum-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%